2018
DOI: 10.1007/s00497-018-00353-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of living apical and basal cell lineages of early proembryos for transcriptome analysis

Abstract: Plant zygotes usually undergo asymmetrical cell division, giving rise to the formation of two daughter cells with distinct developmental cell fate. The small apical cell will develop into the major part of embryo proper, whereas the larger basal cell will divide to form a transient suspensor. Thus, the apical and basal cell lineages are an excellent model to study cell fate determination in relation to zygote polarity. However, the molecular mechanism underlying the differentiation of two distinct cell lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…To date, isolation of tiny early embryos still remains technically challenging. Only a few studies reported the methods for the isolation of early embryos using either laser-capture microdissection (LCM) [ 19 ] or manual isolation [ 19 , 20 ]. However, the LCM equipment is not commonly available, and not suitable for isolating living early embryos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, isolation of tiny early embryos still remains technically challenging. Only a few studies reported the methods for the isolation of early embryos using either laser-capture microdissection (LCM) [ 19 ] or manual isolation [ 19 , 20 ]. However, the LCM equipment is not commonly available, and not suitable for isolating living early embryos.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the key hand-made tools are easy to assemble according to the introduction ( Figure 2 ). This basic setup has been proven to be efficient and reliable in different plants [ 18 , 20 ]. Compared with the other available methods, this procedure offers several advantages: (i) the spatial-temporal characters of suspensor PCD could be quickly detected within 5–6 h, (ii) it can be easily adopted by other researchers due to the simple setup, (iii) it requires affordable equipment for the basic setup, and (iv) this method could also be useful for rapid detection of cell death of abortive embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic studies can now measure and compare transcriptomes in individual cell types [ 64 , 65 , 255 ]. Some examples include comparison of egg to zygote transcriptomes [ 256 ], apical compared with basal cell transcriptomes [ 257 ], determination of an embryo epidermal specific transcriptome [ 258 ], and other subregions of the seed/embryo [ 259 ].…”
Section: Discussionmentioning
confidence: 99%
“…In A. thaliana after the first division of a zygote, auxin is transported toward the apical cell due to polar localization of PIN7 proteins [55]. The apical cell Cells 2020, 9, 606 4 of 16 elongates slightly in the direction of auxin flow [56][57][58][59], however progressive auxin accumulation [60] would break default transverse alignment of microtubules and promote longitudinal division in this way. Interestingly, anisotropic growth of the apical and basal cells seems to be necessary for correct embryogenesis.…”
Section: Cytoskeleton Elements Are Regulated By Auxinmentioning
confidence: 99%